Verbal sexual harrassment: A hidden problem for Turkish adolescent girls - (:unkn) unknown (Taylor and Francis Ltd, 2015)
This study is a descriptive one that seeks to determine how adolescent girls cope with verbal sexual abuse in Turkey. The study sample comprised 500 female secondary school students who agreed to participate in the investigation. Data was obtained via a questionnaire that focused on the background of the respondents, the kinds of verbal sexual abuse they had faced, how they felt afterwards, if they had sought to take any action, what coping strategies they adopted, how they explained the abuse and so on. All of them felt that the sexual abuse was abnormal. After the abuse most of the female students did not seek any kind of help and felt that it cannot be stopped. The respondents have had to make some changes in their life styles and restrict their lives to some extent in order to protect themselves from verbal sexual abuse. Some suggestions are made to address the issue and for improving the situation and viewing verbal sexual abuse as an important social and health problem in different educational and health institutions, the family and society. © 2015 Asian Center for Women's Studies, Ewha Womans University.
Keywords: Adolescence; Coping strategies; Turkey; Verbal sexual abuse; Violence